Curriculum Management of Islamic Boarding School Students of Lamongan Islamic University in Forming Religious Character Based on Ahlussunnah Wal Jama'ah An-Nahdliyah - Sanjaya, Muklis; Fu’adi, Imam; Masrokan Mutohar, Prim; Zaenul Fitri, Agus (International Journal of Educational Research & Social Sciences, 2025)
This research is motivated by the phenomenon of religious character in higher education institutions which has been declining in recent decades, this is influenced by the social and social environment, academic and career pressures, exposure to technology and social media and the lack of adequate religious education. Student Islamic Boarding School (Ponpesma) is a solution related to the decline in morals and ethics of students by instilling character based on Ahlussunnah Wal Jama'ah An-Nahdliyah, this study will discuss how the curriculum design of Ponpesma UNISLA in forming Religious Character Based on Ahlussunnah wal Jama'ah an Nahdliyah, the results of this study indicate that: The form of the curriculum design of Ponpesma UNISLA in forming Religious Character Based on Ahlussunnah wal Jama'ah an Nahdliyah is in the form of formulating objectives as successors to the amaliyah salaf shalih, selecting content with the tricita of Ponpesma UNISLA, organizing synergy policies through UNISLA Chancellor Regulation No. 1 of 2019 Article 95, and evaluation based on graduate competency standards (Ubudiyah, Diniyah, al-Qur'an Practical Exams and Assessment of measurable and systematic religious attitudes. So it can be concluded that the results of this study indicate that the curriculum design of Ponpesma UNISLA based on Ahlussunnah wal Jama'ah an Nahdliyah has been able to form Character Religious students.